Gender and sustainable entrepreneurship intention: insights from Malaysian undergraduates - Latip, Malisah; Yusuf, Aidatul Ashya (John Wiley and Sons Inc, 2024)
Sustainable entrepreneurship is believed to be the solution to the detrimental impact of entrepreneurial activities. The concept underscores the necessity to discover, create and utilise business activities that positively contribute to environmental and societal sustainability. This article seeks evidence of which factors influence sustainable entrepreneurship intention (SEI) and how gender moderates the relationship among sustainability attitude, subjective norms and perceived behavioural control and SEI. The survey was administered to 390 undergraduate students at Malaysian public universities. By performing structural equation modelling analysis, results showed that SEI is influenced by sustainability attitude and perceived behavioural control, whereas subjective norms do not have such an impact. The moderation analysis further discovered that gender only moderates the relationship between sustainable attitude and SEI; the strength of the relationship is stronger among female students. The results of this study offer practical guidance for policymakers and industry stakeholders. Policymakers can use these findings to craft focused initiatives and educational programmes to nurture sustainable entrepreneurship among students, cultivating a future workforce dedicated to ethical business conduct. Industry leaders can draw on the understanding of gender differences in the link between sustainability attitudes and SEI to formulate strategies for attracting and retaining talent inclined towards sustainable practices in their entrepreneurial pursuits.